Small local banks in social media: converting social responsibility into consumer attention and economic outcomes - Kozłowski, Łukasz; Kuchciak, Iwa (Journal of Business Economics and Management, 2021)
This study investigates the thematic content of Facebook disclosures from small local banks (SLBs) in Poland, their impact on Facebook users’ attention, and the economic repercussions for SLBs’ growth and performance. Based on the specificity of SLBs and existing empirical evidence, it hypothesizes that disclosures on socially responsible issues increase customer attention and can be converted into economic outcomes. To verify the posed hypotheses, several data sources are employed, including a hand-collected dataset describing the specificity of Facebook activities from SLBs in Poland between 2010 and 2017, and a stepwise research strategy is implemented. First, models of SLBs’ Facebook disclosures are distinguished. Second, the kinds of social media activities that ensure SLBs’ popularity among Facebook users are determined. Third, the thematic content of SLBs’ Facebook disclosures is related to their growth or performance indicators. The collected evidence shows that SLBs, as expected, can garner attention if they concentrate their social media activities mainly on socially responsible or local issues. Moreover, socially responsible activities and economic outcomes are generally not opposed, but only a careful selection of specific social disclosures can effectively exploit social media to the economic advantage of SLBs.